Produksi Ujaran Siswa Autis - Albab, Suhfi (Universitas Muhammadiyah Prof. DR. HAMKA, 2016)
This study is aimed to determine the speech production in students with autism at Lazuardi GIS Senior High School, Depok. The study is focused on speech production in students with autism in order to have knowledge of the structure and the type of sentences given by students with autism. This research was conducted in Lazuardi GIS Senior High School, Depok in August 2016. This study is formed with a qualitative case study method. The data of this study were collected by conducting a direct observation of speech production activity in students with autism. This involved multifaceted interviews for studies conducted to teachers, friends, and families of students with autism. To be included, all findings are recorded on a sheet of field observations and recording devices. The data for this study are analyzed in the form of the table and also had a described analysis. The speech result of students with autism had been qualified to be a complete sentence consists of a subject and predicate. In addition, the study was found that speech does not have an element of predicate as forms an incomplete sentence. Out of 59 utterances that have been collected, the study had most commonly found utterance directive, as total 32 utterances. As many as 20 representative utterance speech in total, and the study also found the 7 commissive speeches. Moreover, the study did not found the form of expressive and declarative speeches. This is because the students with autism are not able to control their basic emotions in speech production. This resulted in the conclusion, that students with autism utterances produced by the age of 18 years old has become a communicative speech, in which contained messages that could be understood by the other speaker even though the sentence is not complete.